肾癌及脑膜瘤术后并发吉兰-巴雷综合征1例 (Beijing Da Xue Xue Bao Yi Xue Ban, 2019)
Guillain-Barre syndrome (GBS) is an autoimmune disease on the injury of peripheral nerve myelin proteins or axon, of which the acute motor axonal neuropathy (AMAN) as a subtype is of infrequence and an extremely low incidence of post-operation. This article originally reported one case from Peking University People’s Hospital on successful treatment of severe GBS (AMAN) on post-operation with renal carcinoma and meningioma. The diagnostic criteria of AMAN refer to AIDP, of which the feature of AMAN suggests a pure motor nerve dysfunction and significant damage on motor axon. It is reported that infection and surgery may induce GBS. The positive result of IgM and IgG was considered the application of ganglioside and blood-brain barrier might be damaged after meningioma surgery which eased the drug to enter the cerebrospinal fluid circulation and induced lesions, therefore the etiology on this GBS case was of high confidence of administrating ganglioside drugs. Autonomic nerve dysfunctions, such as blood pressure fluctuations and arrhythmia could be caused in GBS, of which about 3%-10% of GBS patients would die. Early use of gamma globulin or plasma exchange was recommended interna-tionally, but recently some new ideas, to some extent, of significance on GBS treatment emerged. However, there was still no consensus on GBS treatment systematically all over the world. Till now, the general treatment program on GBS may be still gamma globulin or plasma exchange and a curious judgment of prognosis is essential in order to make a reasonable plan. That it was usually of no omen on severe autonomic nerve dysfunction must be successively monitored, the same as the management of the respiratory tract and nutrition support. The key measures taken on lung recruitment was postural drainage on this case with a low cost but a qualified effectiveness. This case report aimed to deepen the understanding of AMAN and acquaint the cutting-edge advances on the treatment of GBS, as well as providing successful treatment experience for the prevention on similar cases.